Miniaturized wideband hybrid directional coupler using slow wave structure meandering lines technique - Chong, Jaw Chung (2016)
Branch-line coupler is an important element in modern microwave circuit. A more compact and wideband prototype is preferred, since; it lowers the production cost and could operate well in wider bandwidth. However, most conventional branch line couplers consume bigger spacing and operate in narrow bandwidth. In this research, a wideband three-branch line coupler and four-branch line coupler, which are 20.6 % and 50.2 % respectively, compact than conventional couplers, had been miniaturized using Slow Wave Structure (SWS) and Meandering Line (ML) techniques. The cascade method is implemented on conventional coupler for increasing its bandwidth. The fabricated area of modified three-branch line and fourbranch line coupler is (1729.9 mm2) and (1927.8 mm2), respectively. Both prototypes were fabricated using etching technique. The performance results were obtained using Keysight E5071C VNA (Vector Network Analyzer). Calibration had been done to VNA for all types of measurement. Its important parameters such as return loss |S11|, through |S21|, coupling |S31| and isolation |S41| are studied for both conventional and modified designs, within the frequency range of 1.0 GHz to 5.0 GHz. The AWR Microwave Office Software is used for simulation, and designing the prototypes using 2.4 GHz as centre frequency, where the operating bandwidth remains at 1.5 GHz to 3.5 GHz. The performance of both prototypes were validated by comparing the simulation and measurement results, where, they show good agreement in S-parameters performance similar to the conventional ones, or even better. The modified three-branch line coupler experienced |S11| below -13 dB with operating frequency band of 1.5 GHz, which is 0.1 GHz wider than conventional design performance with 1.4 GHz frequency band, whereas, the modified fourbranch line coupler experienced |S11| below -13 dB with operating frequency band of 2.0 GHz, which is 0.6 GHz wider than conventional design performance with 1.4 GHz frequency band. In conclusion, the modified prototypes are more compact, making it make portable and operates well within wider operating bandwidth.